Barriers and facilitators to the implementation of nurse's role in primary care settings: an integrative review - Erica Busca; Alessia Savatteri; Tania Lorenza Calafato; Beatrice Mazzoleni; Michela Barisone; Alberto Dal Molin (BMC, 2021)
Abstract Background The rapid evolution of the epidemiological picture and the recent SARS-COV-2 pandemic has expressed the vulnerabilities of health systems and focuses attention on the population's needs. The nurse's figure in the care teams is universally identified; however, the implementation of the role within some care settings turns out to be complex and challenging. This integrative review aims to identify the barriers and facilitators in implementing the role of the nurse in primary care settings. Methods An integrative review was conducted on the Medline and Cinahl databases until 9 June 2020. Qualitative, quantitative, and Mixed-method research studies were selected to identify studies related to the barriers and facilitators of the nurse's role in nursing facilities' primary care. For the extraction of the results, the Consolidating Framework for Research Implementation (CFIR) was used to identify the factors that influence implementation in health care. Results Following the duplicates' removal, the search identified 18,257 articles, of which 56 were relevant to the inclusion criteria; therefore, they were included in the summary. The selected studies were conducted in thirteen countries, most from Oceania, Europe, North America, Latin America, and the Caribbean. The barriers reported most frequently concern the nursing profession's regulatory and regulatory aspects within the contexts of care, cultural and organizational aspects, training, and the transfer of specific skills, which were previously designated to doctors. The facilitators are mainly linked to the nurse's adaptability to the various contexts of care, recognizing the patient's role, and the desire to develop multidisciplinary and effective working groups to respond to the health needs of the population in primary care contexts. Conclusion This review highlighted the main barriers and facilitators in implementing the nurse's role in primary care settings. These results offer useful elements for stakeholders to identify effective strategies in preparing programs and activities for implementing the nurse's role, acting on the elements identified as barriers and favouring the aspects that emerge as facilitators.